The ethno-cultural eco-poetry in Leonle Lienlaf, an ecocritical interpretations in several of his poems (2022)
This article will analyse from an ecocritical perspective poems written by Mapuche poet Leonel Lienlaf. Several poems from Se ha despertado el ave de mi corazón (autotranslated into Spanish by the author) will be examined to underline the importance of the intricate connection between human and nature. The symbolic dimension used by the author intertwines with the ethnocultural dimension of the mapuches, which will however remain of secondary importance for the investigation. The article aims to emphasize the centrality of communication between nature and the human that Lienlaf conveys through his poems, one that ultimately becomes a coexistence with the enviroment.